PERENCANAAN STRUKTUR MUSEUM PERMAINAN ANAK TRADISIONAL DI BRINGIN KECAMATAN NGALIYAN - Rusyadi, Imron; Viantoro, Trinugroho Ardin; Kristiawan, Agung; Budirahardjo, Slamet (Jurnal Teknik Sipil Giratory UPGRIS, 2022)
ABSTRACTThe museum is an institution entrusted by the government to store and preserve cultural heritage that is rarely known by the general public. 19 of 1995, a museum is an institution, a place for storing, maintaining, securing and utilizing material evidence of human culture as well as nature and the environment in order to support efforts to protect and preserve the nation's cultural wealth. The "Structure Planning of the Traditional Children's Game Museum in Bringin, Ngaliyan District" has a problem formulation of how to analyze the structural calculations in "Structure Planning of the Bringin Traditional Children's Game Museum, Ngaliyan District". This thesis is planned in accordance with the regulations that apply to buildings including Procedures for Calculation of Concrete Structures for Buildings (SNIÂ 03-2847-2002); Earthquake Resistance Planning Standards for Buildings (SNI 03-1726-2002) and Loading Planning Guidelines for Houses. And Building (PPPURG 1987). In this plan, data analysis uses manual calculations assisted by EExcel and SAP 2000 programs. This plan uses a sand metal roof covering, 12 cm thick floor plate on the 2nd and 3rd floors, while the 4th floor is 15 cm thick, with beam dimensions 35 x 60 , 35 x 50, 35 x 55 cm, and columns using SAP 2000 obtained column dimensions K1 (50cm x 50cm) and K (60cm x 60cm), using 20 D 19 reinforcement for K1 and 24 D 19 reinforcement for K2, Pile foundations, the dimensions of the pile are 30 cm x 30 cm, the depth of the pile of hard soil is 5.4 m and the length of the pile is 6 m.Keywords: building planning, reinforced concrete planning, SAP 2000